2020
DOI: 10.1002/ajb2.1432
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variation impacts trait expression and selection in the legume–rhizobium symbiosis

Abstract: Premise The ecological outcomes of mutualism are well known to shift across abiotic or biotic environments, but few studies have addressed how different environments impact evolutionary responses, including the intensity of selection on and the expression of genetic variance in key mutualism‐related traits. Methods We planted 30 maternal lines of the legume Medicago lupulina in four field common gardens and compared our measures of selection on and genetic variance in nodulation, a key trait reflecting legume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 74 publications
(114 reference statements)
2
16
1
Order By: Relevance
“…Plants that received only sham inoculations had the fewest nodules, and all were pink, nitrogen-fixing nodules; this suggests T173 did not travel between pots, and again, that the naturally occurring rhizobia in the soil are N-fixing. The absence of T173 in the environmental soil matches a previous study that sequenced naturally occuring rhizobia from Medicago lupulina nodules collected at the same field site (Batstone et al 2020a) and found that most nodules contained Ensifer meliloti , or another effective symbiont, Ensifer medicae (Harrison et al 2017). Our results show that priority effects can occur under field conditions, and there are myriad ways that strains might arrive in different orders on plants in natural populations: for example, with rain moving rhizobia from site to site, existing patchiness of soil microbes, or the death of a legume releasing a pulse of rhizobia from its roots.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Plants that received only sham inoculations had the fewest nodules, and all were pink, nitrogen-fixing nodules; this suggests T173 did not travel between pots, and again, that the naturally occurring rhizobia in the soil are N-fixing. The absence of T173 in the environmental soil matches a previous study that sequenced naturally occuring rhizobia from Medicago lupulina nodules collected at the same field site (Batstone et al 2020a) and found that most nodules contained Ensifer meliloti , or another effective symbiont, Ensifer medicae (Harrison et al 2017). Our results show that priority effects can occur under field conditions, and there are myriad ways that strains might arrive in different orders on plants in natural populations: for example, with rain moving rhizobia from site to site, existing patchiness of soil microbes, or the death of a legume releasing a pulse of rhizobia from its roots.…”
Section: Discussionsupporting
confidence: 88%
“…strain T173 (Bromfield et al 2010). Ensifer meliloti strain 1022 was first isolated from Medicago orbicularis growing wild in Greece (Terpolilli et al 2013) but the species has been found associating with M. lupulina in natural populations at KSR (Batstone et al 2020a), while Ensifer T173 was first isolated in Melilotus alba growing wild in Canada, co-occurring in areas with M. lupulina (Bromfield et al 2010). As described in previous experimental work, Ensifer sp.…”
Section: Methodsmentioning
confidence: 99%
“…Batstone et al. (, in this issue) found that the expression of plant genetic variation for nodule number depended on the environment, whereas we find that rhizobium variation contributing to plant growth benefits differed across light environments. Thus, while we arrive at similar broad‐scale conclusions about the importance of context‐dependent genetic variation to mutualism evolution, the particulars of which partner (host vs. symbiont) and traits were different.…”
Section: Discussioncontrasting
confidence: 69%
“…These results indicate that the soil microbial community acts as an agent of selection on critical plant life history traits. Similarly, Batstone et al (2020) examined the potential for different environments to influence selection and genetic variance in nodulation-a key trait reflecting legume investment in symbiosis-in Medicago lupulina. They found that mean and genetic variance for nodulation was greater in the greenhouse, yet selection was stronger in the field.…”
Section: Living Togethermentioning
confidence: 99%